TORETTO'S STREET GANG AMBITION REFLECTED IN THE FAST AND THE FURIOUS MOVIE (2001) DIRECTED BY ROB COHEN: A PSYCHOANALYTIC APPROACH. - SETIAWAN , TEGUH (2010)
The object of the study is a movie The Fast and the Furious movie is directed by Robert Cohen. The study is to reveal how Dominic Toretto's ambition to be a street gang and street racer is reflected in The Fast and the Furious movie directed by Robert Cohen published in 2001. The researcher proposes to analyze ego defense mechanism in a film with the title The Fast and the Furious with Psychoanalytic Approach. There are two objectives: the first is to analyze the film in term of structural elements and the second is to analyze the film based on Psychoanalytic Approach. The researcher employs the descriptive qualitative research as a type of the research. The data sources divided into two, namely primary data source and secondary data source. The primary data source is the events of the movie and script of The Fast and the Furious and the secondary data source is biography of character. The method of collecting data is documentation. The technique of analyzing data is descriptive. The results of the study are as follows. First, based on the structural analysis, Robert Cohen as the director of the movie delivers a moral message about the street gang and street racer and the structural elements are related each other and form a unity. Second, based on Psychoanalytic approach, Robert Cohen reflected the character and characterization in id, ego, superego, anxiety, and ego defense mechanism.